A novel experimental procedure to determine the cohesive law in ENF tests. (20th January 2019) - Arrese, A.; Insausti, N.; Mujika, F.; Perez-Galmés, M.; Renart, J.
Abstract: This study presents a novel method to determine the mode II cohesive law of unidirectional carbon fiber reinforced polymer laminates, employing the End Notched Flexure (ENF) test. The fracture toughness in mode II ( G ) and crack shear displacement ( Δ t ) are determined based on a compliance variation data reduction method (BTBR) by processing the global load displacement curve, without monitoring the crack length and the crack shear displacement during the test. The procedure is validated by finite element analysis including cohesive zone modeling. The results of the method are compared to those obtained with the Direct Method, where the fracture toughness is determined based on the rotations of the load introduction points and the crack shear displacement is directly measured. It is concluded that the proposed data reduction scheme is suitable to obtain the mode II cohesive law using only the load and displacement data obtained from the testing machine, without any external displacement measurement technique and without any assumption of the form of the cohesive law.